PERANCANGAN PROTOTIPE DAPUR PINTAR BERBASIS IOT MENGGUNAKAN NODEMCU ESP8266 DAN APLIKASI BLYNK - Aryo Lukito; Andhika Solihan Asbi Adimart Permana; Seandy Satrio Rianto (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2024)
Industrial revolution 4.0 allows the integration of digital technology with human life through the Internet of Things. One form of IoT application is in kitchen devices. In this case, kitchen safety is the main concern. In this research, an IoT device was developed that can detect gas leaks in the kitchen. The success of previous studies using gas sensors Arduino Uno and MQ2, MQ3 and MQ5 proved to be able to detect gas leaks, but there are still some deficiencies in these devices such as not being connected to mobile devices and efforts to reduce gas levels. Therefore this study adds a feature to monitor room temperature and humidity using the DHT11 sensor, as well as a remote connection feature via a smartphone. In addition, an automatic fan feature is also added to suck up excess gas levels. So that this research is expected to facilitate the process of monitoring the kitchen and reduce the risk of gas leaks which are harmful to health and safety.